2002
DOI: 10.1016/s0741-5214(02)94270-9
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord blood supply in patients with thoracoabdominal aortic aneurysms

Abstract: Objective: In patients with thoracoabdominal aortic aneurysms (TAAAs), the blood supply to the spinal cord is highly variable and unpredictable because of obstructed intercostal and lumbar arteries. This study was performed for the prospective documentation of patent segmental arteries during TAAA repair and the assessment of their functional contribution to the spinal cord blood supply. Methods: TAAA repair was performed in 184 consecutive patients (68 with type I aneurysm, 91 with type II, and 25 with type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(50 citation statements)
references
References 8 publications
0
49
0
1
Order By: Relevance
“…Unfortunately, DP-SCI developed because the postoperative BP values fell significantly below these verified safe thresholds. Postoperative hypotension has been previously identified as a significant risk factor for DP-SCI, 8,11,22,27,28 with up to one They found a significant interindividual variability of such values, ranging from 48 to 110mm Hg, 6,19,29,30 with a higher requirement for those with severe and poorly controlled HTN. 6 Previous data 21,23,31 showed that poorly controlled HTN, a ratio of post operative BP /preoperative BP values of less than 1, and significant BP fluctuations increase the risk of DP-SCI.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, DP-SCI developed because the postoperative BP values fell significantly below these verified safe thresholds. Postoperative hypotension has been previously identified as a significant risk factor for DP-SCI, 8,11,22,27,28 with up to one They found a significant interindividual variability of such values, ranging from 48 to 110mm Hg, 6,19,29,30 with a higher requirement for those with severe and poorly controlled HTN. 6 Previous data 21,23,31 showed that poorly controlled HTN, a ratio of post operative BP /preoperative BP values of less than 1, and significant BP fluctuations increase the risk of DP-SCI.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of the reattachment of critical intercostal arteries (T8-L2 zone) is widely demonstrated [41], and the procedure can be performed either systematically or selectively. The routine reimplant of all patent intercostal arteries in T7-L2 segment proved to reduce paraplegia rate below 10% in some series [42], but it can be time-consuming, and large "Carrel" patches may be susceptible to further dilatation. Therefore, it is questionable whether a large number of reimplanted intercostal arteries justify the effort and the risk for every patient; in particular it would probably be better to avoid unnecessary reimplantations especially in patients with connective tissue disorders.…”
Section: Intercostal Artery Reimplantmentioning
confidence: 99%
“…The collateral network concept for spinal perfusion was developed in the early 2000s [1] and is based on the knowledge that spinal cord perfusion can be ensured by intraspinal and paraspinal arteries in the case of occlusion of segmental arteries. According to this concept, spinal circulation consists of three compartments that communicate longitudinally and horizontally, the intraspinal, the paraspinal intramuscular, and the extramuscular compartment [2].…”
Section: Spinal Cord Perfusionmentioning
confidence: 99%